Geochemistry of the dolerites and the intrusion mechanisms of two major sills in the Secunda coal field - Van Niekerk, Johann le Roux (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Sc.) -- University of Stellenbosch, 1995.